Field report, summer 1995, Thomas Kent - Kent, Thomas H. (Thomas Hugh), 1934-et al (1995)
An annotated list of birds sighted by Thomas Kent dated July 31, 1995. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1995. Epson - sheet feed/flatbed